Planning for UK terror attacks: Analysis of blast and ballistic injuries. Issue 5 (May 2021) - Brewster, C.T.; Forbes, K.; Handford, C.; Scallan, N.; Eskell, M.; Hettiaratchy, S.; Baden, J.
Highlights: Blast patients are more likely to suffer polytrauma than GSW (53% vs 23%), underwent more surgical procedures and utilized double the theatre time on average. Blast injury patients had a higher ITU admission rate and longer length of stay in hospital. The average cost per patient for blast patients was double that of the GSW injury cohort. The workload in mass casualty events is front-loaded with high numbers of damage control surgery, but includes a long tail of ongoing care for multiple specialties. This same burden if felt by intensive care units and must be accounted for in mass casualty events. Major trauma patients must be treated by a multi-disciplinary team from point of wounding. This optimises the quality of their care, chance of survival and outcome. Strategy and resource distribution is key to managing mass casualty events, with frequent multi-speciality trauma meetings including experienced management personnel. Abstract: Terrorist attacks have become more acute, less predictable and frequently involve use of explosives and gunfire to inflict mass casualty to civilians. Resource demand has been reported in Role 3 Medical Facilities but the continued resource required to manage blast and ballistic injuries has not been quantified. This study aimed to assess the resource required for blast and ballistic injuries at the United Kingdom's Role 4 Medical Facility. Military patients admitted to the Queen Elizabeth Hospital (Role 4 Medical Facility) from Afghanistan with blast or ballistic injuries during the 2012 calendar year were retrospectively reviewed. Injury pattern, theatre resource, length of stay and cost analysis were performed. This study included 99 blast and 53 gunshot wound (GSW) patients. Blast patients were more likely to suffer polytrauma than GSW (53% vs 23%), underwent more surgical procedures and utilized double the theatre time. Blast injury patients had a longer length of stay in hospital. The average cost per patient for blast patients was double that of the GSW injury cohort. The Queen Elizabeth experience represents a continuous flow of severely injured military casualties whilst managing concurrent civilian trauma over a long period. This workload has encouraged systematic advancements in managing high numbers of injured patients from point of wounding to rehabilitation. Distribution of resource, theatre planning and multi-disciplinary team working are critical in effectively managing Major Incidents such as terror attacks. Drawing on previous Role 4 Medical Facility experience can aid UK hospitals in terms of strategy and resource distribution.